Pengaruh Kualitas Produk, Citra Merek, Dan Harga Terhadap Kepuasan Konsumen Pada Konsumen Sepatu Nike Di Surabaya - Resanda Putra Sulistiono; Lia Nirawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to identify the extent to which product quality, brand image, and price influence customer satisfaction among Nike shoe consumers in Surabaya. The population for this study was determined to be 674,564 Surabaya residents in the year 2022. Data collection was done using a questionnaire distributed to a sample of 100 respondents. The sampling technique employed was non-probability sampling, specifically purposive sampling. The sample criteria included Surabaya residents aged 20 to 34 who use Nike shoes. The study utilized validity testing, reliability testing using Cronbach’s alpha, normality testing using the Kolmogorov-Smirnov test, multicollinearity testing, heteroskedasticity testing using scatterplot methods, multiple linear regression analysis, coefficient of determination analysis, simultaneous (F) test, and partial (T) test. All statistical analyses were performed using SPSS 23. The results of this study indicate that product quality, brand image, and price collectively have a significant impact on customer satisfaction, with an effect size of 37.744. Specifically, product quality and price individually significantly influence customer satisfaction, with effect sizes of 3.750 and 5.634, respectively. However, the brand image variable does not significantly affect customer satisfaction, with an effect size of 1.301.